Monoculture of Leafcutter Ant Gardens - Mueller, Ulrich G.; Scott, Jarrod J.; Ishak, Heather D.; Cooper, Michael; Rodrigues, Andre [UNESP] (Public Library Science, 2010)
Background: Leafcutter ants depend on the cultivation of symbiotic Attamyces fungi for food, which are thought to be grown by the ants in single-strain, clonal monoculture throughout the hundreds to thousands of gardens within a leafcutter nest. Monoculture eliminates cultivar-cultivar competition that would select for competitive fungal traits that are detrimental to the ants, whereas polyculture of several fungi could increase nutritional diversity and disease resistance of genetically variable gardens.Methodology/Principal Findings: Using three experimental approaches, we assessed cultivar diversity within nests of Atta leafcutter ants, which are most likely among all fungus-growing ants to cultivate distinct cultivar genotypes per nest because of the nests' enormous sizes (up to 5000 gardens) and extended lifespans (10-20 years). In Atta texana and in A. cephalotes, we resampled nests over a 5-year period to test for persistence of resident cultivar genotypes within each nest, and we tested for genetic differences between fungi from different nest sectors accessed through excavation. In A. texana, we also determined the number of Attamyces cells carried as a starter inoculum by a dispersing queens (minimally several thousand Attamyces cells), and we tested for genetic differences between Attamyces carried by sister queens dispersing from the same nest. Except for mutational variation arising during clonal Attamyces propagation, DNA fingerprinting revealed no evidence for fungal polyculture and no genotype turnover during the 5-year surveys.Conclusions/Significance: Atta leafcutter ants can achieve stable, fungal monoculture over many years. Mutational variation emerging within an Attamyces monoculture could provide genetic diversity for symbiont choice (gardening biases of the ants favoring specific mutational variants), an analog of artificial selection.